Reaching across the aisle: Cross‐disciplinary collaboration in otolaryngology research. (19th December 2018) - Kim, Sun Joo; Choi, Won Kyu; Lee, Andrew H.; Yi, Paul H.; Boss, Emily
Abstract : Objectives: Collaboration and diversity of expertise are increasingly emphasized in the production of successful research. However, the degree of cross‐disciplinary collaboration in otolaryngology research is unknown. In this study, we quantify cross‐disciplinary collaboration in otolaryngology publications. Methods: We retrospectively analyzed authorship and study characteristics for all original articles published from January 2014 to December 2016 in three key peer‐reviewed otolaryngology journals: Laryngoscope, Otolaryngology–Head & Neck Surgery, and JAMA Otolaryngology–Head & Neck Surgery . Author affiliations and online searches were used to determine author's primary discipline. Subspecialty topic of article, study design, and funding sources were also recorded. Fisher exact test was used to compare characteristics of articles with and without cross‐disciplinary authorship. Results: A total of 2, 378 articles were reviewed, of which 1, 312 (55%) articles had one or more cross‐disciplinary collaborators. Among articles with cross‐disciplinary collaboration, the greatest representation of disciplines was from other medical specialties (1, 109, 50.9%), epidemiology/biostatistics (266, 12.2%), pathology/histology (175, 8.0%), biologic sciences (168, 7.7%), and radiology/imaging (144, 6.6%). Cross‐disciplinary studies had a significantly greater proportion of articles on the topic of head and neck compared to studies without collaboration ( P < 0.0001). The proportion of funded studies was significantly greater among articles with collaboration compared to articles without collaboration ( P < 0.0001). Conclusion: The majority of articles published during a 3‐year period in three influential otolaryngology journals had cross‐disciplinary collaboration. There is potential opportunity for further leveraging expertise, funding opportunities, and dissemination of key findings through collaborative research. Level of Evidence: NA Laryngoscope, 129:1800–1805, 2019